A Meir-Keeler Type Common Fixed Point Result in Dislocated Metric Space - Panthi, Dinesh (Journal of Nepal Mathematical Society, 2018)
Meir and E. Keeler [11] generalized the Banach Contraction Principle [1] with the notion of weakly uniformly strict contraction which is famous as a (ε - δ) contraction. In this article, we establish a Meir- Keeler type common fixed point result in dislocated metric space which generalize and extend similar fixed point results in the literature.